Ecological assessment and DNA barcoding of major pollinators of Ziziphus mauritiana in Bangladesh - Rahman, Md. Towhidur; Aslam, Abu Faiz Md. (Nepalese Journal of Zoology, 2025)
Ziziphus mauritiana, a key fruit crop, depends on insect pollination, yet its pollinator diversity remains understudied in Bangladesh. This study combines ecological observation and DNA barcoding to assess the diversity and genetics of its pollinators. A total of 33 species from Hymenoptera, Diptera, Lepidoptera, and Coleoptera were identified, with bees being the most dominant (55.2%), followed by flies (29.1%). Peak pollinator activity occurred between 10:00 AM and 12:00 PM, with Apis species and Chrysomya megacephala showing sustained activity, highlighting their ecological significance. Molecular identification of the seven most frequent pollinator species was confirmed through cytochrome c oxidase subunit I (COI) gene sequencing. Nucleotide composition analysis revealed a pronounced AT bias (71.6%), consistent with typical insect mitochondrial DNA composition. Genetic distance and t-SNE analyses showed clear taxonomic clustering, with interspecific nucleotide differences ranging from 0.1064 to 0.3770, supported by haplotype network and phylogenetic tree. Haplotype analysis revealed 1 to 4 mutational steps within Apis, while distant species exhibited between 28 and 77 mutational steps. Additionally, the sequence similarity within Apis was 84%, in contrast to the 74% similarity in wasps. These findings enhance our understanding of Z. mauritiana pollination ecology and highlight the value of integrating ecological surveys with molecular tools for effective pollinator conservation.